Surface‐to‐tunnel electrical resistance tomography measurements. Issue 4 (1st January 2015) - Simyrdanis, K.; Tsourlos, P.; Soupios, P.; Tsokas, G.; Kim, J.‐H.; Papadopoulos, N.
ABSTRACT: In this work we examine the applicability of surface‐to‐tunnel electrical resistance tomography measurements for imaging subsurface targets. Various issues of this special arrangement are discussed and explored by means of numerical model simulations, experimental measurements in a tank, and a field application. The geometrical factor was considered as a filter during the generation of the protocols in order to reject electrode combinations and problematic measurements. Different electrode arrays are examined and compared for various targets, and we concluded that, for the tested cases, the pole–tripole electrode arrangement produced superior results. Additional tests showed that the maximum distance between the electrode lines is strongly related to the nature of the prospected target. Furthermore, the study showed that the tunnel size affects the measured data and needs to be taken into account when processing surface‐to‐tunnel data, and the full incorporation of the tunnel into a 3D model proved to be the optimum among the tested correction schemes. Finally, we present a real case study involving electrical resistance tomography surface‐to‐tunnel measurements, and results are in comparable agreement with the findings of the tests with numerical and experimental data.